Shuffled frog leaping algorithm for solving economic load dispatch problem / Mohammad Ariffin Aizat Ezanee - Ezanee, Mohammad Ariffin Aizat (2015)
This thesis presents the solution to Economic Load Dispatch (ELD) problem in order to minimize the generation cost. Shuffled Frog Leaping Algorithm (SFLA) is proposed to solve Economic Load Dispatch (ELD) problem. The proposed SFLA method is developed using MATLAB programming. This SFLA method is tested on IEEE 30 bus system and the results show that it can solve ELD problem by providing minimum cost. This method provides a better result compared to Classical Method using lamda iteration and Genetic Algorithm (GA).